(untitled) (Itinera, 2017)
Dealing with the visual aspects in his writing process, this is not only because of the cultural context but also because of his background that Jan Fabre literature is also a visual literature. The analyses of Mon corps, mon gentil corps, dis-moi… focus on the sight sense in a linguistic point of view, and those of Another Sleepy Dusty Delta Day tend to highlight the plasticity of the writing that goes beyond the text itself.